Kemas Ulang Informasi Manfaat Daun Katuk untuk Produksi Air Susu Ibu (ASI) - Herawati, Yunila; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this paper is to describe the stages of repackaging information and also designing and producing a printed information or booked. The benefits of this paper are useful for breastfeeding mothers and users who need it. The research method used is descriptive, data collected through literature study (articles in PDF, HMTL, DOC, TXT, PS). The stages of repackaging information about katuk leaf benefits for the production of breast milk are: (1) identifying user needs, (2) defining the topic/title of information to be covered. This determination usually will involve ideas and input from experts staff, manufacturers of packaging products, information, product consumers and information services and employees, (3) collect information from any sources that match with topic, (4) the selection and analysis of information, (5) determine the form of repackaged information either printed or non-printed, (6) examination/editing, (7) print with a more attractive shape.Keyword: ASI, information repackaging, katuk leaf.